Designs of Low Delay Cosine Modulated Filter Banks and Subband Amplifiers - Ling, B.; Al Hosni, K.; Dam, Hai (Universitat Politecnita de Catalunya, 2011)
This paper proposes a design of a low delay cosine modulated filter bank and subband amplifier coefficients for digital audio hearing aids denoising applications. The objective of the design is to minimize the delay of the filter bank. Specifications on the maximum magnitude of both the real and the imaginary parts of the transfer function distortion and the aliasing distortion of the filter bank are imposed. Also, the constraint on the maximum absolute difference between the desirable magnitude square response and the designed magnitude square response of the prototype filter over both the passband and the stopband is considered. The subband amplifier coefficients are designed based on a least squares training approach. The average mean square errors between the noisy samples and the clean samples is minimized. Computer numerical simulation results show that our proposed approach could significantly improve the signal-to-noise ratio of digital audio hearing aids.